QCD sum rules calculation of heavy Λ semileptonic decay - Dosch, H. G.; Ferreira, E.; Nielsen, M.; Rosenfeld, R. [UNESP] (Elsevier B.V., 1998)
We set up sum rules for heavy lambda decays in a full QCD calculation which in the heavy quark mass limit incorporates the symmetries of heavy quark effective theory. For the semileptonic Λc decay we obtain a reasonable agreement with experiment. For the Λb semileptonic decay we find at the zero recoil point a violation of the heavy quark symmetry of about 20%. © 1998 Published by Elsevier Science B.V. All rights reserved.